Changes in menopausal risk factors in early postmenopausal osteopenic women after 13 months of high-intensity exercise: The randomized controlled ACTLIFE-RCT - Hettchen, Michael; von Stengel, Simon; Kohl, Matthias; Murphy, Marie H.; Shojaa, Mahdieh; Ghasemikaram, Mansour; Bragonzoni, Laura; Benvenuti, Francesco; Ripamonti, Claudio; Benedetti, Maria Grazia; Julin, Mikko; Risto, Tapani; et al. (Clinical Interventions in Aging, 2021)
The menopausal transition is a critical period in women’s lives. Exercise might be the most promising non-pharmaceutic intervention to address the large variety of risk factors related to the pronounced estradiol decline during peri-and early-postmenopause. The aim of this study was to determine the effect of an 18-month multipurpose exercise program on risk factors and symptoms related to the menopausal transition. Fifty-four women 1–5 years postmenopause with osteopenia or osteoporosis were randomly assigned 1) to a high impact weight-bearing/high-intensity/velocity resistance training group (EG: n=27) exercising three times a week or 2) to an attendance control group (CG: n=27) that performed low-intensity exercise once a week. Both groups were supplemented with cholecalciferol and calcium. The primary study endpoint was bone mineral density (BMD) at lumbar spine (LS) and total hip, secondary outcomes were lean body mass (LBM), total and abdominal body percentage, metabolic syndrome Z-Score (MetS-Z), menopausal symptoms and muscle strength and power. Due to COVID-19, the study was stopped after 13 months. We observed significant effects for BMD-LS (EG: 0.002±.018 versus CG: −.009±0.018 mg/cm2, p=0.027) but not for BMD total hip (EG: −0.01±.016 versus CG: −.009±0.020 mg/cm2, p=0.129). LBM improved significantly in the EG and decreased in the CG (0.39±1.08 vs −0.37±1.34 kg, p=0.026). Total and abdominal body fat improved significantly in the EG and was maintained in the CG (−1.44±1.49 vs −0.02±1.55 kg, p=0.002 and-1.50±2.33 vs 0.08±2.07 kg, p=0.011). Significant effects in favor of the EG were also determined for menopausal symptoms (p=0.029), hip/leg extension strength (p<0.001) and power (p<0.001). However, changes of the MetS-Z did not differ significantly (p=0.149) between EG and CG. In summary, with minor exceptions, we demonstrated the effectiveness of a multipurpose exercise protocol dedicated to early-postmenopausal women on various risk factors and complaints related to the menopausal transition.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Bone mineral density; Early postmenopause; Multipurpose exercise

Dynamic Resistance Exercise and Bone Mineral Density at the Lumbar Spine in Postmenopausal Women: A systematic review and meta-analysis with special emphasis to exercise parameters - Kemmler, Wolfgang; Shojaa, Mahdieh; Kohl, Matthias; Schöne, Daniel; von Stengel, Simon (Osteologie, 2020)
Exercise might be the most promising non-pharmacologic agent in fracture prevention of older people. Dynamic resistance exercise (DRT) is a recognised component of most exercise protocols, be it in fall prevention or bone strengthening exercise protocols. However, the most optimum DRT protocol to address Bone Mineral Density (BMD) in postmenopausal women has yet to be fully validated. Hence the aim of this systematic review and meta-analysis aimed (1) to determine the effect of dynamic resistance exercise (DRT) on BMD at the lumbar spine (LS) in postmenopausal women (b) to identify exercise component particularly effective to trigger favourable LS-BMD changes and (3) to derive evidence-based recommendations for optimised training protocols. A systematic review of the literature according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement included 8 different databases (PubMed, Scopus, Web of Science, Cochrane, Science Direct, Eric, ProQuest und Primo) without language restrictions. We included (a) controlled trials of isolated DRT with at least one exercise and one control group, (b) interventions of six months or longer, (c) BMD assessments at the LS at least before and after the study, (d) studies that focused on postmenopausal women and/or reported dedicated results for this group.Primary outcome measure for the meta-analysis was standardised mean difference (SMD) for BMD-changes at lumbar spine (LS). Further we conducted sub-analysis to determine modulators of the exercise effect on BMD using subgroup-analysis. We included 'intervention length', 'type of DRT', 'training frequency', 'exercise intensity' and 'exercise volume' split into two or three meaningful categories in the analyses. In summary, 17 articles with 20 exercise and 18 control groups were eligible. We observed a significant effect (p<.001) of moderate size (SMD: (0.59; 95%-CI: 0.26-0.92) for LS-BMD changes. Apart from one exception we did not observe significant or relevant (p<.20) differences between the categories of the given modulators. Lower training frequency (<2 sessions/week) resulted in significantly higher BMD changes at LS, however, compared to higher training frequency (≥2 sessions/week). The work provided further evidence for a significant, albeit only moderate, DRT effect on LS-BMD in postmenopausal women. We attribute this suboptimum result to the high variation within the eligible studies with trials that did not properly apply basic exercise principle in their research. Unfortunately, sub-analysis did not result in reliable data. In contrast to all present studies, lower training frequency was significantly more favourable to increase BMD at LS compared with higher training frequency. We conclude that sub-analyses of meta-analytical evaluation were unable to identify promising exercise components and thus derive optimum training protocols for bone strengthening due to the close interaction of exercise parameters.
CRIS-Team Scopus Importer:2020-08-28
Keywords: bone mineral density; exercise components; osteoporosis; Resistance exercise

Effect of different types of exercise on bone mineral density in postmenopausal women: A systematic review and meta-analysis - Shojaa, Mahdieh; von Stengel, Simon; Schöne, Daniel; Kohl, Matthias; Kemmler, Wolfgang (Osteologie, 2020)
Postmenopausal women face a high risk of bone loss. Exercise has a beneficial effect to prevent bone deterioration in elderly women. This study was conducted to investigate the effect of different types of exercise on bone mineral density at the lumbar spine and femoral neck in postmenopausal women. This review followed the guidelines recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and was registered in advance in the International prospective register of systematic reviews (PROSPERO) (ID: CRD42018095097). Literature searches with no language restriction were conducted through PubMed, Scopus, Web of Science, Cochrane, Science Direct, Eric, ProQuest, and Primo up to March 1 2019 using related MeSH terms and key words. Controlled trials with ≥ 6 months intervention duration among postmenopausal women that comprised at least one exercise and one control group were included in this study. Meta-analyses were performed using random-effects models and effect sizes calculated using the standardised mean difference (SMD). Seven categories of exercise were classified and used in sub-group analyses. P-values < 0.05 were considered statistically significant. Seventy-five studies were included, assessing the bone mineral density of 5300 (range of mean age: 50-79) postmenopausal women who performed exercise or control protocols. Interventions ranged from six to 30 months and the most common exercise frequency was three sessions per week. The majority of studies employed multicomponent exercise interventions. Results of the meta-analyses showed a significant effect (SMD = 0.37, 95%-CI: 0.25-0.50) for lumbar spine and femoral neck (SMD = 0.33, 0.23-0.43) (all P < 0.0001). Sub-group analysis revealed large heterogeneity and no significant differences in exercise categories at the lumbar spine (P = 0.36) and femoral neck (P = 0.43). However, weight-bearing exercise + jumping + resistance training exhibited the largest effect (SMD = 0.71, 0.33-1.10) at the lumbar spine. Moreover, non-weight-bearing combined + resistance exercise revealed the largest effect (SMD = 0.68, 0.16-1.19) at the femoral neck. Contrary to our expectation, jumping alone indicated a greater decrease in bone mineral density compared to the control group at both the lumbar spine (-0.07, -0.46-0.32) and femoral neck (-0.12, -0.62-0.37). In conclusion, the current study provided a positive small effect of exercise on bone mineral density at the lumbar spine and femoral neck. Findings from sub-group analyses suggest larger benefits in multicomponent interventions that include weight-bearing and resistance training exercises compared to them as a single mode of exercise. Unequal numbers of studies were found for each category (e. g. jumping: two trials; dynamic resistance training: 15 trials), affecting the comparison between them. Therefore, findings should be interpreted with caution; they are not yet generalizable to specific types of exercise.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Bewegung; Knochen; Metaanalyse; Postmenopause; Training

Effect of exercise training on bone mineral density in post-menopausal women: A systematic review and meta-analysis of intervention studies - Shojaa, Mahdieh; von Stengel, Simon; Schöne, Daniel; Kohl, Matthias; Barone, Giuseppe; Bragonzoni, Laura; Dallolio, Laura; Marini, Sofia; Murphy, Marie H.; Stephenson, Aoife; Mänty, Minna; Julin, Mikko; et al. (Frontiers in Physiology, 2020)
Osteoporosis is a major health problem in post-menopausal women (PMW). Exercise training is considered a cost-effective strategy to prevent osteoporosis in middle aged-older people. The purpose of this study is to summarize the effect of exercise on BMD among PMW. A comprehensive search of electronic databases was conducted through PubMed, Scopus, Web of Science, Cochrane, Science Direct, Eric, ProQuest, and Primo. BMD changes (standardized mean differences: SMD) of the lumbar spine (LS) femoral neck (FN) and/or total hip were considered as outcome measures. After subgroup categorization, statistical methods were used to combine data and compare subgroups. Seventy-five studies were included. The pooled number of participants was 5,300 (intervention group: n = 2,901, control group: n = 2,399). The pooled estimate of random effect analysis was SMD = 0.37, 95%-CI: 0.25–0.50, SMD = 0.33, 95%-CI: 0.23–0.43, and SMD = 0.40, 95%-CI: 0.28–0.51 for LS, FN, and total Hip-BMD, respectively. In the present meta-analysis, there was a significant (p < 0.001), but rather low effect (SMD = 0.33–0.40) of exercise on BMD at LS and proximal femur. A large variation among the single study findings was observed, with highly effective studies but also studies that trigger significant negative results. These findings can be largely attributed to differences among the exercise protocols of the studies. Findings suggest that the true effect of exercise on BMD is diluted by a considerable amount of studies with inadequate exercise protocols.
CRIS-Team Scopus Importer:2020-07-24
Keywords: BMD; Bone mineral density; Exercise; Post-menopausal women; Training

Effects of different exercise intensity on bone mineral density in adults: a comparative systematic review and meta-analysis - Kast, Stephanie; Shojaa, Mahdieh; Kohl, M.; von Stengel, S.; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Klöckner, N.; Lange, U.; Middeldorf, S.; Peters, S.; et al. (Osteoporosis international, 2022)
Purpose: The primary objective of the present systematic review and meta-analysis was to determine the effect of differing exercise intensity on (areal) bone mineral density (BMD) at lumbar spine and hip in adults by a comparative meta-analysis. Methods: A systematic review of the literature according to the PRISMA statement included: (a) exercise trials, (b) with ≥two study arms that compared different exercise intensities, (c) intervention ≥6 months, (d) BMD assessments at lumbar spine (LS) or hip. Five electronic databases were scanned without language restrictions up to July 2021. The present analysis of exercise intensity was conducted as a mixed-effect meta-analysis and applied “type of exercise” and “study duration” as moderator in subgroup analyses. Outcome measures were standardized mean differences (SMD) for BMD changes at the LS, and hip. Results: Eleven exercise studies with 26 study arms were included. Although the effect of high-intensity exercise was more pronounced on LS-BMD (SMD: 0.19, 95%-CI: 0.61 to -0.23) and hip-ROI (0.17, 0.38 to -0.04), we did not observe significant differences between the groups (LS-BMD: p=0.373 and hip-BMD: p=0.109). We observed a substantial level of heterogeneity between the trials for LS- but not for hip-BMD. Applying “type of exercise” and “study duration” as moderators did not significantly modify the differences between low and high exercise intensity on BMD at LS or hip. Conclusion: There is insufficient evidence for a superior effect of high-intensity exercise on areal BMD at lumbar spine and hip in people aged 50 years and older. Varying exercise intensity with periods of lower exercise intensity intermitted by higher intensity might be a promising option to address the issue of exercise intensities in intervention studies.
CRIS-Team Scopus Importer:2022-03-25
Keywords: BMD; Exercise; Intensity; Meta-analysis; Type of exercise

Effects of Different Types of Exercise on Bone Mineral Density in Postmenopausal Women: A Systematic Review and Meta-analysis. - Kemmler, Wolfgang; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon (Calcified Tissue International, 2020)
In this sub-analysis of a comprehensive meta-analysis, we aimed to determine the effect of different types of exercise on (areal) bone mineral density (BMD) in postmenopausal women. A systematic review of the literature according to the PRISMA statement included (a) controlled trials, (b) with at least one exercise and one control group, (c) intervention ≥ 6 months, (d) BMD assessments at lumbar spine (LS), femoral neck (FN) or total hip (TH), (e) in postmenopausal women. Eight electronic databases were scanned without language restrictions up to March 2019. The present subgroup analysis was conducted as a mixed-effect meta-analysis with "type of exercise" as the moderator. The 84 eligible exercise groups were classified into (a) weight bearing (WB, n = 30) exercise, (b) (dynamic) resistance exercise (DRT, n = 18), (c) mixed WB&DRT interventions (n = 36). Outcome measures were standardized mean differences (SMD) for BMD-changes at LS, FN and TH. All types of exercise significantly affect BMD at LS, FN and TH. SMD for LS average 0.40 (95% CI 0.15-0.65) for DRT, SMD 0.26 (0.03-0.49) for WB and SMD 0.42 (0.23-0.61) for WB&DRT. SMD for FN were 0.27 (0.09-0.45) for DRT, 0.37 (0.12-0.62) for WB and 0.35 (0.19-0.51) for WB&DRT. Lastly, SMD for TH changes were 0.51 (0.28-0.74) for DRT, 0.40 (0.21-0.58) for WB and 0.34 (0.14-0.53) for WB&DRT. In summary, we provided further evidence for the favorable effect of exercise on BMD largely independent of the type of exercise. However, in order to generate dedicated exercise recommendations or exercise guideline, meta-analyses might be a too rough tool.
EVALuna2:420611

Effects of dynamic resistance exercise on bone mineral density in postmenopausal women: a systematic review and meta-analysis with special emphasis on exercise parameters - Shojaa, Mahdieh; von Stengel, Simon; Kohl, M.; Schöne, Daniel; Kemmler, Wolfgang (Osteoporosis international, 2020)
This systematic review and meta-analysis set out to determine the effect of dynamic resistance exercise (DRT) on areal bone mineral density (aBMD) in postmenopausal women and derive evidence-based recommendations for optimized training protocols. A systematic review of the literature according to the PRISMA statement included (a) controlled trials, (b) of isolated DRT with at least one exercise and one control group, (c) with intervention durations ≥ 6 months, (d) aBMD assessments at lumbar spine or proximal femur, (e) in cohorts of postmenopausal women. We searched eight electronic databases up to March 2019 without language restrictions. The meta-analysis was performed using a random-effects model. Standardized mean differences (SMD) for BMD changes at lumbar spine (LS), femoral neck (FN), and total hip (TH) were defined as outcome measures. Moderators of the exercise effects, i.e., “intervention length,” “type of DRT,” “training frequency,” “exercise intensity,” and “exercise volume,” were addressed by sub-group analyses. The study was registered in the international prospective register of systematic reviews (PROSPERO) under ID: CRD42018095097. Seventeen articles with 20 exercise and 18 control groups were eligible. SMD average is 0.54 (95% CI 0.22–0.87) for LS-BMD, 0.22 (0.07–0.38) for FN-BMD, and 0.48 (0.22–0.75) for TH-BMD changes (all p ≤ 0.015). While sub-group analysis for FN-BMD revealed no differences within categories of moderators, lower training frequency (< 2 sessions/week) resulted in significantly higher BMD changes at LS and TH compared to higher training frequency (≥ 2 sessions/week). Additionally, free weight training was significantly superior to DRT devices for improving TH-BMD. This work provided further evidence for significant, albeit only low–moderate, effects of DRT on LS-, FN-, and TH-BMD. Unfortunately, sub-analysis results did not allow meaningful exercise recommendations to be derived. This systematic review and meta-analysis observed a significant low–moderate effect of dynamic resistance exercise on bone mineral density changes in postmenopausal women. However, sub-group analyses focusing on exercise characteristics found no results that enable the derivation of meaningful exercise recommendations in the area of exercise and osteoporosis prevention or therapy.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Bone mineral density; Dynamic resistance exercise; Exercise characteristics; Postmenopausal women

Effects of High-Intensity Aerobic Exercise and Resistance Training on Cardiometabolic Risk in Early-Postmenopausal Women - Hettchen, Michael; von Stengel, Simon; Kohl, M.; Murphy, M. H.; Shojaa, Mahdieh; Ghasemikaram, Mansour; Bragonzoni, L.; Benvenuti, F.; Ripamonti, C.; Benedetti, G.; Julin, M.; Risto, T.; et al. (Deutsche Zeitschrift für Sportmedizin, 2021)
Purpose: The menopausal transition is a critical period in wo-men’s lives. The central aim of the present study was to evaluate the effect of a multimodal exercise protocol on the cardiometa-bolic risk factor potentially related to menopausal transition in early postmenopausal women. Methods: Fifty-four (54) early-postmenopausal women (54.0±1.8 years) were randomly assigned to two groups: (1) exercise group (EG: n=27) which conducted a high intensity aerobic and resistance training three times/week and (2) active control group (CG: n=27) exercising once a week with low exercise inten-sity. Besides bone density, the main variable of this project, the outcome variable in this thesis was also cardiometabolic risk, as summarized by the Metabolic Syndrome (MetS) Z-Score. We applied Intention-to-Treat (ITT) and Per Protocol Analyses (PPA) with multiple imputation and used standardized mean differences to illustrate the effects. Results: After 16 weeks of exercise two participants (EG: n=1; CG: n=1) were lost to follow-up. Effects for the MetS Z-Score were moderate (EG:-0.36±1.36 vs. CG: 0.51±2.28; SMD: 0.47, 95% CI:-0.08 to 1.03), albeit borderline non-significant (ITT: p=.089; PPA: p=.060). Conclusion: The present multimodal exercise protocol just fai-led to affect the MetS Z-Score and its underlying cardiometabolic risk factors. Whether this result can be generalized to the entire cohort of early-postmenopausal women or whether it has to be attributed to the only moderately high exercise intensity during the early weeks of the intervention along with a relatively short intervention period remains to be evaluated.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Menopausal transition; Metabolic syndrome; MetS Z-Score

Effects of Hormone Therapy and Exercise on Bone Mineral Density in Healthy Women-A Systematic Review and Meta-analysis. - Born, Clara; Jakob, Franz; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Kerschan-Schindl, Katharina; Lange, Uwe; Thomasius, Friederike; Kemmler, Wolfgang (Journal of Clinical Endocrinology and Metabolism, 2022)
CONTEXT: There is some evidence that an adequate "anabolic hormonal milieu" is essential for the mechanosensitivity/transduction/response of bone tissue. OBJECTIVE: This work aimed to determine whether enhancing hormone therapy (HT) with exercise increases the isolated effect of HT on bone mineral density (BMD) at the lumbar spine (LS) and femoral neck (FN). METHODS: A comprehensive search of 6 electronic databases according to the PRISMA statement up to April 28, 2021, included controlled trials longer than 6 months with 3 study arms: (a) HT, (b) exercise, and (c) HT plus exercise (HT + E). Apart from HT, no pharmaceutic therapy or diseases with relevant osteoanabolic or osteocatabolic effect on bone metabolism were included. The present analysis was conducted as a random-effects meta-analysis. Outcome measures were standardized mean differences (SMD) for BMD changes at the LS and FN. RESULTS: Our search identified 6 eligible studies (n = 585). Although the effect of HT + E was more pronounced in the LS (SMD: 0.19; 95% C,: -0.15 to 0.53) and FN-BMD (0.18; -0.09 to 0.44) compared to the HT group, we did not observe significant differences between the 2 groups. We observed a low (I2: 29%) or moderate (I2: 49%) level of heterogeneity between the trials for FN or LS. CONCLUSION: We do not observe a significant effect of HT + E vs HT alone. We largely attribute this result to varying HT supplementation and hormonal status. Bearing in mind that synergistic/additive effects between HT and mechanical stimulation can only be expected in situations of hormonal insufficiency, further clinical studies should consider baseline endogenous estrogen production but also HT dosing more carefully.
EVALuna2:511005

Efficacy and Safety of Low Frequency Whole-Body Electromyostimulation (WB-EMS) to Improve Health-Related Outcomes in Non-athletic Adults. A Systematic Review - Kemmler, Wolfgang; Weißenfels, Anja; Willert, Sebastian; Shojaa, Mahdieh; von Stengel, Simon; Filipovic, Andre; Kleinoeder, Heinz; Berger, Joshua; Froehlich, Michael (Frontiers in Physiology, 2018)
Exercise positively affects most risk factors, diseases and disabling conditions of middle to advanced age, however the majority of middle-aged to older people fall short of the exercise doses recommended for positively affecting cardio-metabolic, musculoskeletal and neurophysiological fitness or disabling conditions. Whole-Body Electromyostimulation (WB-EMS) may be a promising exercise technology for people unable or unmotivated to exercise conventionally. However, until recently there has been a dearth of evidence with respect to WB-EMS-induced effects on health-related outcomes. The aim of this systematic review is to summarize the effects, limitations and risks of WB-EMS as a preventive or therapeutic tool for non-athletic adults. Electronic searches in PubMed, Scopus, Web of Science, PsycINFO, Cochrane and Eric were run to identify randomized controlled trials, non-randomized controlled trials, meta-analyses of individual patient data and peer reviewed scientific theses that examined (1) WB-EMS-induced changes of musculoskeletal risk factors and diseases (2) WB-EMS-induced changes of functional capacity and physical fitness (3) WB-EMS-induced changes of cardio-metabolic risk factors and diseases (4) Risk factors of WB-EMS application and adverse effects during WB-EMS interventions. Two researchers independently reviewed articles for eligibility and methodological quality. Twenty-three eligible research articles generated by fourteen research projects were finally included. In summary, thirteen projects were WB-EMS trials and one study was a meta-analysis of individual patient data. WB-EMS significantly improves muscle mass and function while reducing fat mass and low back pain. Although there is some evidence of a positive effect of WB-EMS on cardio-metabolic risk factors, this aspect requires further detailed study. Properly applied and supervised, WB-EMS appears to be a safe training technology. In summary, WB-EMS represents a safe and reasonable option for cohorts unable or unwilling to join conventional exercise programs. However, much like all other types of exercise, WB-EMS does not affect every aspect of physical performance and health.
EVALuna2:214336

Efficacy of Whole-Body Electromyostimulation (WB-EMS) on Body Composition and Muscle Strength in Non-athletic Adults. A Systematic Review and Meta-Analysis - Kemmler, Wolfgang; Shojaa, Mahdieh; Steele, James; Berger, Joshua; Fröhlich, Michael; Schöne, Daniel; von Stengel, Simon; Kleinöder, Heinz; Kohl, Matthias (Frontiers in Physiology, 2021)
This systematic review and meta-analysis set out to determine the efficacy on whole-body electromyostimulation (WB-EMS) on body composition and strength parameters in non-athletic cohorts. A systematic review of the literature according to the PRISMA statement included (a) controlled trials, (b) WB-EMS trials with at least one exercise and one control group, (c) WB-EMS as primary physical intervention, (d) WB-EMS with at least six electrodes covering most muscle groups, (e) non-athletic cohorts. We searched eight electronic databases up to June 30, 2020, without language restrictions. Standardized mean differences (SMD) for muscle mass parameters, total body fat mass, maximum leg extension, and trunk extension strength were defined as outcome measures. In summary, 16 studies with 19 individual WB-EMS groups representing 897 participants were included. Studies vary considerably with respect to age, BMI, and physical conditions. Impulse protocols of the studies were roughly comparable, but training frequency (1–5 sessions/week) and intervention length (6–54 weeks) differed between the studies. SMD average was 1.23 (95%-CI: 0.71–1.76) for muscle mass, 0.98 (0.74–1.22) for maximum leg, and 1.08 (0.78–1.39) for maximum trunk extension strength changes (all p < 0.001). SMD for body fat changes (−0.40, [−0.98 to 0.17]), however, did not reach significance. I2 and Q-statistics revealed substantial heterogeneity of muscle and fat mass changes between the trials. However, rank and regression tests did not indicate positive evidence for small-study bias and funnel plot asymmetries. This work provided further evidence for significant, large-sized effects of WB-EMS on muscle mass and strength parameters, but not on body fat mass. Clinical Trial Registration: ClinicalTrials.gov, PROSPERO; ID: CRD42020183059.
CRIS-Team Scopus Importer:2021-03-19
Keywords: body composition; body fat mass; exercise; lean body mass; muscle strength; whole-body electromyostimulation

Exercise effects on bone mineral density in men - Mages, Michelle; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Klöckner, Nicole; Lange, Uwe; Middeldorf, Stefan; et al. (Nutrients, 2021)
In contrast to postmenopausal women, evidence for a favorable effect of exercise on Bone Mineral Density (BMD) is still limited for men. This might be due to the paucity of studies, but also to the great variety of participants and study characteristics that may dilute study results. The aim of the present systematic review and meta-analysis was to evaluate the effect of exercise on BMD changes with rational eligibility criteria. A comprehensive search of six electronic databases up to 15 March 2021 was conducted. Briefly, controlled trials ≥6 months that determined changes in areal BMD in men >18 years old, with no apparent diseases or pharmacological therapy that relevantly affect bone metabolism, were included. BMD changes (standardized mean differences: SMD) of the lumbar spine (LS) and femoral neck (FN) were considered as outcomes. Twelve studies with 16 exercise and 12 control groups were identified. The pooled estimate of random-effect analysis was SMD = 0.38, 95%-CI: 0.14–0.61 and SMD = 0.25, 95%-CI: 0.00–0.49, for LS and FN, respectively. Heterogeneity between the trials was low–moderate. Funnel plots and rank and regression correlation tests indicate evidence for small study publication bias for LS but not FN-BMD. Subgroup analyses that focus on study length, type of exercise and methodologic quality revealed no significant difference between each of the three categories. In summary, we provided further evidence for a low but significant effect of exercise on BMD in men. However, we are currently unable to give even rough exercise recommendations for male cohorts.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Bone mineral density; Exercise; Men; Overview

Exercise effects on bone mineral density in older men: a systematic review with special emphasis on study interventions - Kemmler, Wolfgang; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon (Osteoporosis international, 2018)
This systematic review detected only limited positive effects of exercise on bone mineral density in older men. Further, based on the present literature, we were unable to suggest dedicated exercise prescriptions for this male cohort that might differ from recommendations based on studies with postmenopausal women. The primary aim of this systematic review was to determine the effect of exercise on bone mineral density (BMD) in healthy older men. A systematic review of the literature according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement included only randomized or non-randomized controlled trials of exercise training ≥ 6 months with study groups of ≥ eight healthy men aged 50 years or older, not using bone-relevant pharmacological therapy, that determined BMD by dual-energy X-ray absorptiometry. We searched PubMed, Scopus, Web of Science, Cochrane, Science Direct, and Eric up to November 2016. Risk of bias was assessed using the PEDro scale. We identified eight trials with 789 participants (PEDro-score, mean value 6 of 10) which satisfied our eligibility criteria. Studies vary considerably with respect to type and composition of exercise. Study interventions of six trials were considered to be appropriate for successfully addressing BMD in this cohort. Between-group differences were not or not consistently reported by three studies. Three studies reported significant exercise effects on BMD for proximal femur; one of them determined significant differences between the exercise groups. None of the exercise trials determined significant BMD effects at the lumbar spine. Based on the present studies, there is only limited evidence for a favorable effect of exercise on BMD in men. More well-designed and sophisticated studies on BMD in healthy older men have to address this topic. Further, there is a need to define intervention quality standards and implement a universal scoring system that allows this pivotal determinant to be addressed much more intensively.
EVALuna2:214335

Exercise Reduces the Number of Overall and Major Osteoporotic Fractures in Adults. Does Supervision Make a Difference? Systematic Review and Meta-Analysis - Hoffmann, Isabelle; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Clausen, Juergen; Lange, Uwe; Middeldorf, Stefan; et al. (Journal of Bone and Mineral Research, 2022)
The purpose of this systematic review and meta-analysis (PROSPERO ID: CRD42021250467) was to evaluate the effects of exercise on low-trauma overall and major osteoporotic fractures (hip, spine, forearm, or humerus fractures) and to determine the corresponding effect of supervision of the exercise program. Our systematic search of six literature databases according to the PRISMA guideline was conducted from January 1, 2013 (ie, date of our last search) to May 22, 2021, and included controlled clinical exercise trials with (i) individuals aged ≥45 years, (ii) cohorts without therapies/diseases related to fractures, (iii) observation periods of ≥3 months, and (iv) the number of low-trauma fractures listed separately for the exercise (EG) and control (CG) groups. We included 20 intervention studies with 21 EGs and 20 CGs comprising a pooled number of participant-years of n = 11.836 in the EG and n = 11.275 in the CG. The mixed-effects conditional Poisson regression revealed significant effects of exercise on low-trauma overall incidence (rate) ratio (IR 0.67, 95% confidence interval [95% CI] 0.51–0.87) and major osteoporotic fractures IR (0.69, 95% CI 0.52–0.92). Heterogeneity between the trials was moderate for low-trauma overall (I2 = 40%) and negligible (I2 < 1%) for major osteoporotic fractures. Supervision of the exercise program plays a significant role in the reductions of overall and major osteoporotic fractures with IR about twice as favorable in the predominately supervised (IR 0.44; 95% CI 0.27–0.73 and 0.38; 0.19–0.76) versus the predominately non-supervised exercise trials (IR 0.83; 95% CI 0.60–1.14 and 0.82; 0.64–1.05). In summary, the present study provides evidence for the positive effect of exercise on low-trauma overall and major osteoporotic fractures in middle aged to older adults. Supervision of the exercise program is a crucial aspect in exercise programs on fracture reduction. Thus, home-based exercise protocols should increasingly implement online classes to ensure widely consistent supervision and monitoring of the exercise program. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2022-09-23
Keywords: EXERCISE; LOW-TRAUMA FRACTURE; OSTEOPOROTIC FRACTURES; OVERALL FRACTURES

The effect of different training frequency on bone mineral density in older adults. A comparative systematic review and meta-analysis - Zitzmann, Anna Lena; Shojaa, Mahdieh; Kast, Stephanie; Kohl, Matthias; von Stengel, Simon; Borucki, Diana; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Middeldorf, Stefan; et al. (Bone, 2022)
Exercise frequency is a key aspect of exercise protocols. In this systematic review and meta-analysis, we determined the effect of training frequency on (areal) bone mineral density (BMD) at lumbar spine (LS) and hip. Reviewing seven electronic databases up to April 2021, we conducted a systematic review of the literature according to the PRISMA statement. Inclusion criteria were (a) controlled exercise trials (b) with at least two study arms that compared low versus high exercise frequency, (c) an intervention ≥6 months and (d) BMD assessments at lumbar spine (LS) or hip. The analysis was conducted as a mixed-effect meta-analysis and used “type of exercise” and “study duration” as moderators in subgroup analyses. Standardized mean differences (SMD) for LS- and hip-BMD changes were defined as outcome measures. Seven studies with 17 exercise groups were included in the analysis. We observed significantly higher effects of high (≥2 sessions/week) vs. low net training frequency (1–<2 sessions/week) exercise on LS- (SMD 0.55, 95%-CI: 0.20–0.90) but not hip-BMD (0.19, −0.06 to 0.45). Study duration was found to be a significant moderator for the effect of training frequency at LS- but not hip-BMD. In parallel, the type of exercise moderately influences the effect of training frequency on LS- but not on hip-BMD. We observed a superior effect of higher net training frequency on BMD. Longer exercise exposition increases this effect. Considering e.g. holidays, indisposition or other temporary absence, exercise programs on osteoporosis should provide at least 3 sessions/week/year to allow a net training frequency of more than two sessions/week. Study registration: PROSPERO (CRD42021246804).
CRIS-Team Scopus Importer:2021-10-22
Keywords: Bone mineral density; Exercise; Guideline; Training frequency

Whole-body electromyostimulation and protein supplementation favorably affect sarcopenic obesity in community-dwelling older men at risk: the randomized controlled FranSO study - Kemmler, Wolfgang; Weißenfels, Anja; Teschler, Marc; Willert, Sebastian; Bebenek, Michael; Shojaa, Mahdieh; Kohl, Matthias; Freiberger, Ellen; Sieber, Cornel; von Stengel, Simon (Clinical Interventions in Aging, 2017)
Background: Sarcopenic obesity (SO) is a geriatric syndrome characterized by the disproportion between the amount of lean mass and fat mass. Exercise decreases fat and maintains muscle mass; however, older people fail to exercise at doses sufficient to affect musculoskeletal and cardiometabolic risk factors. The aim of this study was to evaluate the effect of whole-body electromyostimulation (WB-EMS), a time-efficient, joint-friendly and highly individualized exercise technology, on sarcopenia and SO in older men.Materials and methods: A total of 100 community-dwelling northern Bavarian men aged >= 70 years with sarcopenia and obesity were randomly (1-1-1) assigned to either 16 weeks of 1) WB-EMS and protein supplementation (WB-EMS&P), 2) isolated protein supplementation or 3) nonintervention control. WB-EMS consisted of 1.5x20 min (85 Hz, 350 mu s, 4 s of strain to 4 s of rest) applied with moderate-to-high intensity while moving. We further generated a daily protein intake of 1.7-1.8 g/kg/body mass per day. The primary study end point was Sarcopenia Z-Score, and the secondary study end points were body fat rate (%), skeletal muscle mass index (SMI) and handgrip strength.Results: Intention-to-treat analysis determined a significantly favorable effect of WB-EMS&P (P < 0.001) and protein (P=0.007) vs control. Both groups significantly (P < 0.001) lost body fat (WB-EMS&P: 2.1%; protein: 1.1%) and differed significantly (P<0.004) from control (0.3%). Differences between WB-EMS&P and protein were significant for the Sarcopenia Z-Score (P=0.39) and borderline nonsignificant (P=0.051) for body fat. SMI increased significantly in both groups (P, 0.001 and P=0.043) and decreased significantly in the control group (CG; P=0.033); differences between the verum groups and control were significant (P <= 0.009). Handgrip strength increased in the WB-EMS group (1.90 kg; P < 0.001; P=0.050 vs control) only. No adverse effects of WB-EMS or protein supplementation were recorded.Conclusion: WB-EMS&P is a safe and efficient method for tackling sarcopenia and SO in older men. However, the suboptimum effect on functional parameters should be addressed by increased voluntary activation during WB-EMS application.
EVALuna2:33281
Keywords: sarcopenia; sarcopenic obesity; exercise; electrostimulation; older people